Is the mainstream construction of mood disorders resistant to systemic thinking? - Fellin, Lisa C.; Zizevskaia, Ekaterina; Galbusera, Laura (Frontiers in Psychiatry, 2024)
In this study we explore how the diagnostic category of mood disorders is constructed in two handbooks of Psychopathology as an example of the mainstream construction of psychopathology. Despite the increasing criticism and lack of evidence, the debunked chemical imbalance theory of the etiology of depression still dominates the professional and pop/folk understanding and interventions. We analysed the breadth of the inference field and the type of etiopathogenetic contents of the explanations of mood disorders using the "1to3" Coding System (Ugazio et al. 2020). Our findings show that the dominant explanations draw almost exclusively onto monadic explanations, followed by limited dyadic ones. Intrapersonal etiopathogenetic contents prevailed, and biomedical explanations were dominant in both textbooks. We critically discuss the underpinnings of these results and address the clinical implications of these biased representations, as well as potential alternative approaches to psychopathology.